Diurnal Rainfall Response to the Physiological and Radiative Effects of CO2 in Tropical Forests in the Energy Exascale Earth System Model v1. Issue 10 (24th May 2022) - Harrop, Bryce E.; Burrows, Susannah M.; Calvin, Katherine; Kooperman, Gabriel J.; Leung, L. Ruby; Maltrud, Mathew E.; Shi, Xiaoying; Tang, Jinyun; Tang, Qi; Wang, Hailong; Zhu, Qing
Abstract: Understanding how the connection between rainfall and tropical forests will respond to increasing CO2 concentrations is a key element in understanding how the tropical water cycle will respond to increasing CO2 . The plant physiological and radiative impacts of CO2 on rainfall patterns over tropical forest regions are examined in the Energy Exascale Earth System Model version 1.1 (E3SMv1.1‐BGC) biogeochemistry experiments. Composite analysis reveals a dampening of the diurnal cycle of rainfall over the Amazon, Congo, and Maritime Continent in response to rising CO2 levels, regardless of the sign of total rainfall change. A full factorial model experiment confirms that the CO2 radiative and CO2 plant physiological effects can individually or jointly reduce the magnitude of the rainfall diurnal cycle, though the physical pathway giving rise to the reduction differs between the two effects. For the physiological response, stomatal closure reduces evapotranspiration, which dries the boundary layer and raises the lifting condensation level. These effects combine to reduce deep convective rainfall during its peak occurrence in the late daytime to early nighttime period. For the radiative response, a relative reduction in daytime Convective Available Potential Energy (consistent with a reduction in the diurnal temperature range) leads to less frequent triggering of deep convection and a reduction of rainfall diurnal amplitude. These diurnal rainfall changes are structurally similar across seasons, and show little sensitivity to representation of nutrient coupling for the land biogeochemistry. In agreement with previous findings, the physiological response has only minor impact on extreme rainfall relative to the radiative response. Plain Language Summary: The distribution of rainfall in time and space is one of the key features of interest in the climate system. Simulations using the biogeochemistry‐enabled version of the U.S. Department of Energy's Energy Exascale Earth System Model are used to explore how increasing atmospheric CO2 concentrations impact the daily cycle of rainfall over the tropical forest regions. Increasing CO2 not only warms the climate system, but also reduces the amount of transpiration from plants. These two effects are examined in isolation and are both found to reduce the daily peak in rainfall, dampening the cycle overall. The warming response is shown to make the atmosphere less favorable to convection, which reduces rainfall, while the reduced transpiration dries out the lower atmosphere, which also reduces rainfall. Key Points: Physiological and radiative effects of CO2 both dampen the diurnal cycle of rainfall in tropical forest regions Physiological effect of CO2 reduces transpiration, dries boundary layer, and raises the lifting condensation level, decreasing deep convective rainfall Radiative effect of CO2 reduces Convective Available Potential Energy leading to reductions in deep convective frequency and rainfall